Short-term cutaneous vasodilatory and thermosensory effects of topical methyl salicylate - Versteeg, Ninja; Wellauer, Vanessa; Wittenwiler, Selina; Aerenhouts, Dirk; Clarys, Peter; Clijsen, Ron (Frontiers in Physiology, 2024)
Introduction: Methyl salicylate, the main compound of wintergreen oil, is widely used in topical applications. However, its vascular and thermosensory effects are not fully understood. The primary aim was to investigate the effects of topical methyl salicylate on skin temperature (Tskin), skin microcirculation (MCskin) and muscle oxygen saturation (SmO2) compared to a placebo gel. The secondary aim was to assess thermosensory responses (thermal sensation, thermal comfort) and to explore to which extent these sensations correspond to the physiological responses over time. Methods: 21 healthy women (22.2±2.9 years) participated in this single-blind, randomized controlled trial. Custom-made natural wintergreen oil (12.9%), containing methyl salicylate (>99%) and a placebo gel, one gram each, were applied simultaneously to two paravertebral skin areas (10x5cm, Th4-Th7). Tskin (infrared thermal imaging), MCskin (laser speckle contrast imaging) and SmO2 (deep tissue oxygenation monitoring) and thermosensation (Likert scales) were assessed at baseline (BL) and at 5-min intervals during a 45min post-application period (T0-T45). Results: Both gels caused an initial decrease in Tskin, with Tskin(min) at T5 for both methyl salicylate (BL-T5: Δ-3.36°C) and placebo (BL-T5: Δ-3.90°C), followed by a gradual increase (p<.001). Methyl salicylate gel resulted in significantly higher Tskin than placebo between T5 and T40 (p<.05). For methyl salicylate, MCskin increased, with MCskin(max) at T5 (BL-T5: Δ88.7%). For placebo, MCskin decreased (BL-T5: Δ-17.5%), with significantly lower values compared to methyl salicylate between T0 and T45 (p<.05). Both gels had minimal effects on SmO2, with no significant differences between methyl salicylate and placebo (p>.05). Thermal sensation responses to topical methyl salicylate ranged from ‘cool’ to ‘hot’, with more intense sensations reported at T5. Conclusion: The findings indicate that topical methyl salicylate induces short-term cutaneous vasodilation, but it may not enhance skeletal muscle blood flow. This study highlights the complex sensory responses to its application, which may be based on the short-term modulation of thermosensitive transient receptor potential channels.